Communicating with older people about positive mental health - Pettigrew, S.; Donovan, Robert; Pescud, M.; Newton, R.; Boldy, Duncan (Emerald Group Publishing Ltd, 2012)
Purpose – In response to a call for greater attention to the mental health promotion needs of older people, this study aims to identify those aspects of mental health messages that may be particularly effective with older audiences. Design/methodology/approach – Individual interviews and focus groups were conducted with 111 Australians aged 40 years and older. Findings – A low level of knowledge relating to mental health issues and the confounding of mental health with mental illness resulted in participants stating a preference for health experts, government officials, and high-profile and “everyday” individuals who have successfully recovered from mental illness as spokespeople for mental health messages. A common theme was that spokespersons should have evident and extensive knowledge of mental illness, either through qualifications, occupation, or personal experience.